An Analysis of Speech Acts in the Conversation between Habibie and Ainun in the Film Entitled Habibie and Ainun 2012 - ., I MADE DWI JAYA PRADITYA; ., Dra. Luh Putu Artini, MA., Ph.D.; ., Prof. Dr.I Nyoman Adi Jaya Putra, MA (Jurnal Pendidikan Bahasa Inggris, 2014)
Kata Kunci : Speech Acts, Analysis, Habibie Ainun This study aimed to analyze the types of speech acts and the classification of illocutionary speech acts occurred in the conversation of Habibie and Ainun in the film entitled Habibie and Ainun 2012. This study was a descriptive qualitative done on naturalistic inquiry on social phenomenon. The data were analyzed based on the theory of direct and indirect speech acts proposed by Yule (1996) and the analysis of the classification of illocutionary speech acts proposed by Searle (1977) consists of representative, directive commissive, expressive and declaration. Findings of this study showed there were 196 utterances of type of speech acts where the type of direct speech acts were 129 utterances (66%), meanwhile the type of indirect speech acts were 67 utterances (34%). There were totally 158 utterances analyzed as illocution where representatives were 90 utterances (51%), commisives were 39 utterances (25%), directive were 24 utterances (15%), expressive were 15 utterances (9%), and there was no declaration (0%). This study showed that the direct speech acts were the most dominant type of speech acts rather than the type of indirect speech act. In the types of illocutionary speech acts, representatives were the most dominant rather that the others types of illocutions. keyword : Speech Act, Analysis, Habibie Ainun